2018
DOI: 10.1016/j.chest.2017.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Two Siblings With Interstitial Lung Disease

Abstract: A 52-year-old white woman and her 61-year-old white brother separately presented with gradually worsening dyspnea on exertion and cough, and evidence of interstitial lung disease on chest imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In some cases, pulmonary disease has been the clinical manifestation that drives diagnosis in adults. Progressive dyspnea (with ILD on imaging) prompted a clinical workup and resulting diagnosis of ASMD in two adult siblings age 52 and 61 years, [ 32 ]. Pulmonary morbidities in chronic ASMD, including respiratory infections and respiratory failure, contribute to early mortality [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, pulmonary disease has been the clinical manifestation that drives diagnosis in adults. Progressive dyspnea (with ILD on imaging) prompted a clinical workup and resulting diagnosis of ASMD in two adult siblings age 52 and 61 years, [ 32 ]. Pulmonary morbidities in chronic ASMD, including respiratory infections and respiratory failure, contribute to early mortality [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, careful review of the literature indicated that such lung appearance of chronic visceral ASMD has been noticed previously. Callahan et al described in 2018 two siblings with ILD in the course of chronic visceral ASMD [ 15 ]. One of them experienced recurrent spontaneous pneumothorax and HRCT revealed upper-lobe-predominant paraseptal emphysema in addition to lower-lobe ILD.…”
Section: Discussionmentioning
confidence: 99%